Evaluation of Central Corneal Thickness Using Corneal Dynamic Scheimpflug Analyzer Corvis ST and Comparison with Pentacam Rotating Scheimpflug System and Ultrasound Pachymetry in Normal Eyes - Ayong Yu; Weiqi Zhao; Giacomo Savini; Zixu Huang; Fangjun Bao; Weicong Lu; Qinmei Wang; Jinhai Huang (Journal of Ophthalmology)
Purpose. To assess the repeatability and reproducibility of central corneal thickness (CCT) measurements by corneal dynamic Scheimpflug analyzer Corvis ST in normal eyes and compare the agreement with Pentacam rotating Scheimpflug System and ultrasound pachymetry. Methods. 84 right eyes underwent Corvis ST measurements performed by two operators. The test-retest repeatability (TRT), within-subject coefficient of variation (CoV), and intraclass correlation coefficient (ICC) were used to evaluate the intraoperator repeatability and interoperator reproducibility. CCT measurements also were obtained from Pentacam and ultrasound pachymetry by the first operator. The agreement between the three devices was evaluated with 95% limits of agreement (LoA) and Bland-Altman plots. Results. Corvis ST showed high repeatability as indicated by TRT ≤ 13.0 μm, CoV < 0.9%, and ICC > 0.97. The interoperator reproducibility was also excellent. The CoV was <0.9%, and ICC was >0.97. Corvis ST showed significantly lower values than Pentacam and ultrasound pachymetry (P<0.001). The 95% LoA between Corvis ST and Pentacam or ultrasound pachymetry were −15.8 to 9.5 μm and −27.9 to 12.3 μm, respectively. Conclusions. Corvis ST showed excellent repeatability and interoperator reproducibility of CCT measurements in normal eyes. Corvis ST is interchangeable with Pentacam but not with ultrasound pachymetry.